4
$\begingroup$

The problem is:

Given this equation find the possible values of $x$. $$\log_{2}\left ( \frac{x+2}{x-1} \right )+\log_{2}\left [ (x+2)(x-1) \right ]=2$$

First I defined the domain of the function.

  1. The denominator $x-1$ must not be zero: $x-1\neq0$.

  2. The fraction $\frac{x+2}{x-1}$ must be bigger than zero: $\frac{x+2}{x-1}>0$.

  3. The product $(x+2)(x-1)$ must be bigger than zero: $(x+2)(x-1)>0$.

In the end I concluded that the domain should be $\left ]-\infty,-2\right [\cup \left ]1,+\infty\right[$.

Then I sarted to solve:

$$\begin{align*} \log_{2}\left ( \frac{x+2}{x-1} \right )&+\log_{2}\left [ (x+2)(x-1) \right ]=2 \\ &\iff \log_{2}(x+2)-\log_{2}(x-1)+\log_{2}(x+2)+\log_{2}(x-1)=2\\ &\iff 2 \cdot \log_{2}(x+2)=2\\ &\iff \log_{2}(x+2)=1 \\ &\iff x+2=2^1\\ &\iff x=2-2\\ &\iff x=0. \end{align*}$$

This result is not in the domain! Where I miss?

$\endgroup$
4
  • $\begingroup$ Put every step into wolfram alpha and look where it becomes wrong, learn to help yourself :-) $\endgroup$
    – Listing
    Oct 29, 2011 at 22:41
  • $\begingroup$ So the answer is: for no (real) value of $x$. $\endgroup$ Oct 29, 2011 at 22:43
  • 1
    $\begingroup$ I took the liberty of putting some periods to your text. This may sound rude, but it's for your own good: You wouldn't write an entire paragraph of text with no periods, would you? It's better that your learn to write math such that it flows like a "normal" text now, rather than when you hand in an assignment and get "add more periods and commas" as a comment from your teacher. $\endgroup$
    – kahen
    Oct 29, 2011 at 22:50
  • $\begingroup$ @Yuval: The first "if and only if" does not hold over the entire domain, only on $(1,\infty)$. $\endgroup$ Oct 29, 2011 at 22:54

2 Answers 2

3
$\begingroup$

One problem is that you can have both the product and the fraction be valid arguments for $\log_2$, but the individual factors/denominator/numerator not be valid arguments. Specifically, if $x\lt -2$, then neither $x-1$ nor $x+2$ are valid arguments, so you cannot take the first step in general.

Instead, why not work those identities in the other direction? $$\begin{align*} \log_2\left(\frac{x+2}{x-1}\right) + \log_2\Bigl( (x+2)(x-1)\Bigr) &= \log_2\left(\left( \frac{x+2}{x-1}\right)(x+2)(x-1)\right)\\ &= \log_2\left(\bigl(x+2\bigr)^2\right). \end{align*}$$ Now, if $x+2\gt0$ (and hence, if $x\gt 1$, then this is equal to $2\log_2(x+2)$, from which you conclude that $\log_2(x+2) = 1$, hence $x+2=2$, hence $x=0$, but that is not in the domain.

What does that mean? It means that you cannot find a solution with $x+2\gt 0$.

What if $x+2\lt 0$, though? Then simply go from $\log_2((x+2)^2) = 2$ to $(x+2)^2 = 2^2 = 4$, and hence $-(x+2) = 2$, or $x+2=-2$, hence $x=-4$. This is in the domain, and satisfies $x+2\lt 0$.

Indeed, note that if $x=-4$, then $\frac{x+2}{x-1} = \frac{-2}{-5} = \frac{2}{5}$, and $(x+2)(x-1) = (-2)(-5) = 10$, so you have that the left hand side is $$\log_2(2/5) + \log_2(10) = \log_2(20/5) = \log_2(4) = 2,$$ so $x=-4$ is a solution.

$\endgroup$
1
$\begingroup$

If $x>1$, then $\log_2\left(\dfrac{x+2}{x-1}\right) = \log_2(x+2)-\log_2(x-1)$.

If $x<-2$ then $\log_2\left(\dfrac{x+2}{x-1}\right) = \log_2\left(\dfrac{-x-2}{1-x}\right) = \log_2(-x-2)-\log_2(1-x)$.

A similar thing applies to the logarithm of the product.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.